Effect of Age at Slaughter on Various Carcass Characteristics of Hassan Sheep - Shanthesha, Kandikere M; Ruban, Savariraj W; Guruprasad , Rachaiah; Shivappanayaka, Honnebagi B; Naveen, Kumar S; Shivakumar, Rekhyanaik; Sudarshan, Siggiriyappa (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was carried out to evaluate the influence of age at slaughter on various carcass characteristics of Hassan sheep. A total of 32 male Hassan sheep 12 each in 3 different age groups, viz., 6-8 months (T1), 12-15 months (T2) and 30-32 months (T3) were slaughtered as per standard procedure. The pre-slaughter weight (PSW), hot carcass weight (HCW), dressing percent (DP) and loin eye area (LEA) revealed a significant difference (p<0.05) between the three age groups. Age group T3 recorded the highest PSW and HCW, whereas T2 recorded the highest DP (49.74%) and LEA (12.68 cm2). The age at slaughter was found to have a significant (p<0.05) effect on the weight of the non-carcass components and the offal weights. Group T3 recorded a significantly higher (p<0.05) weight of liver, head, feet, blood, heart, kidney, spleen, brain followed by T2 and T1. It was evident that in T3 group the per cent of major primal cuts, viz., shoulder, leg and loin cuts decreased significantly (p<0.05), whereas there was an increase in per cent of neck and rack cuts clearly indicating that in older/ aged animals the per cent of valuable cuts decreased. No significant difference was observed in the linear carcass measurements with respect to T1 and T2, whereas T3 recorded significantly higher measurements as compared to T1 with respect to all the linear carcass measurements. Based on the results it is concluded that the optimal age of slaughter of Hassan sheep is 12-15 months to obtain better carcass yield and yields of valuable cuts with good muscling.